Congruity and Divergence in Perceptions of Adolescent Romantic Experience Between Chinese Parents and Adolescents. Issue 4 (July 2020) - Liu, Ting; Fuller, Jeffrey; Hutton, Alison; Grant, Julian
This qualitative research article explored the convergences and divergences of perceptions of adolescent romantic experience between a group of adolescents and parents in China. One-to-one, in-depth interviews were conducted with 38 adolescents (aged 15-18 years; 26 girls, 12 boys) and 27 parents (aged 40-52 years; 16 mothers, 11 fathers) from the urban areas of a northern Chinese city. Data analysis was conducted using thematic analysis and interpreted using a socio-ecological approach. Four major themes were identified: opportunities and risks, acceptable versus unacceptable sexual intimacy, generational difference, and girls' vulnerability and "self-respect." In these themes, congruity and divergence of perceptions were found between the groups of adolescents and parents. These perceptions were largely influenced by traditional cultural beliefs of education, sexuality, gender, and family as well as the current socio-cultural context of modernization and globalization in China. The findings provide implications regarding how to support both adolescents and parents in managing adolescent romantic experience for adolescent health-promoting romantic and sexual behaviors.